Effects of Morus nigra L. in Bone Healing - Costa, Jeferson Cardoso; Pereira, Bárbara Caroliny; Soares, Evelise Aline; Gonçalves, Nalielle Lohana Serafini; Esteves, Alessandra; Rossi Junior, Wagner Costa (Journal of Morphological Sciences, 2019)
Morus nigra L., popularly known as blackberry, mulberry or blackberry bush, is a plant species widely used by folk medicine. Although there are few scientific studies that denote its therapeutic features, an important highlight of black mulberry is the recurrent use of tea leaves in popular environment for treatment of climacteric because it is considered a source of substances with estrogenic activity, which, if deficient, decreases osteoblastic action. Thus, the objective of the present study was to analyze the effect of the infusion of the leaves of M. nigra L. on bone repair experimental models. Twenty female Wistar rats (Rattus norvegicus), ∼ 100 days old, were submitted to fracture with bone loss in the left fibula. After that, they ingested tea leaves of M. nigra L. for 30 days without interruption. The animals suffered euthanasia after the treatment period. The results showed a significant healing of fractures in all animals that ingested the tea, when compared with other groups. In this way, it is possible to suggest that M. nigra L. tea is able to trigger a positive response in bone repair mechanism; however, it is not possible to state at what level this positive interference occurs, since mechanisms of its action have not yet been elucidated, thus requiring more specific studies on the phytotherapeutic effects of this plant.
Keywords: healing bone; morus; bone fracture; medicinal plants